Coastal wetlands : an integrated ecosystem approach - Perillo, G. M. E. (Elsevier, 2019)
Coastal Wetlands, Second Edition: An Integrated and Ecosystem Approach provides an understanding of the functioning of coastal ecosystems and the ecological services that they provide. As coastal wetlands are under a great deal of pressure from the dual forces of rising sea levels and the intervention of human populations, both along the estuary and in the river catchment, this book covers important issues, such as the destruction or degradation of wetlands from land reclamation and infrastructures, impacts from the discharge of pollutants, changes in river flows and sediment supplies, land clearing, and dam operations.
Keywords: Estuarine restoration.; Coastal zone management.; Wetland ecology.; Coasts.; elektronické knihy; electronic books